2005
DOI: 10.1021/jp054429u
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the Radical−Radical Reaction, O(3PJ) + OH(X2ΠΩ) → O2 + H, at Temperatures down to 39 K

Abstract: The kinetics of the reaction between O atoms and OH radicals, both in their electronic ground state, have been investigated at temperatures down to ca. 39 K. The experiments employed a CRESU (Cinétique deRéaction en Ecoulement Supersonique Uniforme) apparatus to attain low temperatures. Both reagents were created using pulsed laser photolysis at 157.6 nm of mixtures containing H2O and O2 diluted in N2 carrier gas. OH radicals were formed by both direct photolysis of H2O and the reaction between O(1D) atoms and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
76
1
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 98 publications
(91 citation statements)
references
References 41 publications
11
76
1
3
Order By: Relevance
“…They showed that magnetic fields of several thousand Gauss suppress inelastic collision rates by about two orders of magnitude. In a recent study [33], we reported quantum dynamics calculations of reaction (1) for T = 10 − 600 K and found no significant decrease of the rate coefficient in the temperature range 39 − 10 K, in accordance with conclusions of a recent experimental study by Carty et al [52]. Our calculations for reaction probabilities were in excellent agreement with those of Xu et al [53] for collision energies E c > 0.012 eV.…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…They showed that magnetic fields of several thousand Gauss suppress inelastic collision rates by about two orders of magnitude. In a recent study [33], we reported quantum dynamics calculations of reaction (1) for T = 10 − 600 K and found no significant decrease of the rate coefficient in the temperature range 39 − 10 K, in accordance with conclusions of a recent experimental study by Carty et al [52]. Our calculations for reaction probabilities were in excellent agreement with those of Xu et al [53] for collision energies E c > 0.012 eV.…”
Section: Introductionsupporting
confidence: 91%
“…[33] and experimental conclusions of Ref. [52], that the rate coefficient of reaction (1) is unlikely to vanish for T < 10 K. We also note that the Langevin rate coefficient is in semiquantitative agreement with the inelastic rate coefficient in the range T = 100−1000 K. The difference is less than 30 %.…”
Section: B Classical Capture Modelsupporting
confidence: 82%
“…The experimental rate constant is well determined between 140 and 300 K decreasing from 7 × 10 −11 cm 3 molecule −1 s −1 at 140 K to 3 × 10 −11 cm 3 molecule −1 s −1 at 300 K. Between 40 and 140 K, the reaction has been studied in a CRESU (Cinétique de Réaction en Ecoulement Supersonique Uniforme) apparatus (Carty et al 2006) leading to a value of around 3.5(±1.0) × 10 −11 cm 3 molecule −1 s −1 which however has large uncertainties. Quasi-classical trajectory calculations give good agreement with experiment between 300 K and 3000 K (Troe & Ushakov 2001) and between 40 K and 140 K (Jorfi et al 2008) but the relatively good agreement at low temperature may be fortuitous.…”
Section: Experimental and Theoretical Determination Of The Rate Coeffmentioning
confidence: 99%
“…The thermal rate coefficient of this reaction has recently been measured in the laboratory down to temperatures of 39 K (Carty et al 2006), where it remains rapid. In subsequent ab initio theoretical calculations, Xu et al (2007) found a much smaller rate at temperatures below 30 K and suggested that this might solve the problem of missing O 2 in cold interstellar clouds.…”
Section: O 18 O Column Density and O 18 O Abundancementioning
confidence: 99%